Negotiating meanings and examining practice of 'arts across the curriculum'. Issue 3 (2nd September 2017) - Buck, Ralph; Snook, Barbara Helen
Abstract: Examining practice, within education, is complex and never straightforward. It is not a surprise that when we conduct research, we discover new and contrary meanings. For the last 16 months we have been examining different means for supporting teaching and learning of the arts in primary schools. Our aim was to better understand how to teach the arts across the curriculum. We made a plan, we gained ethical approval, found several schools to work with, and interviewed teachers and principals. Our research has a specific interest in documenting and understanding how the arts are taught across the curriculum. We were most interested in working with teachers, principals and children who were implementing an 'arts across the curriculum programme'. In short, what we found was that teachers, principals, curriculum and us, all had different meanings of what was meant by teaching the arts across the curriculum.